The Effect of Product Quality, Electronic Word of Mouth and Lifestyle on Purchasing Decisions in Generation Z - Rizki, Muhammad; Santosa, Awan (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Product quality is a characteristic of a product or service that depends on its ability to satisfy customer needs, whether stated directly or implied. Product quality influences purchasing decisions. Encouragement of product quality has become a need that must be met by companies, if consumers do not want it, they must switch to other competing products which are considered to have better product quality, the higher the product quality they have. This research aims to analyze the influence of product quality, electronic word of mouth, and lifestyle on the decision to purchase iPhone brand cellphones in generation Z. The population in this study is all iPhone users in generation Z using a purposive sample. This research used 100 respondents. The data collection technique used was a survey method with research tools used in the form of questionnaires with a Likert scale, and analyzed using IBM SPSS Statistics 25 Software. The results of this research analysis show that product quality has a positive and significant influence on purchasing decisions. Apart from that, electronic word of mouth has a positive and significant influence on purchasing decisions. Furthermore, lifestyle has a positive and significant influence on purchasing decisions.